ENVIRONMENTAL SYSTEM ENGINEERING (ESE): MODELING AND OPTIMIZATION OF A TEXTILE EFFLUENT DISCOLORATION PROCESS BY SORPTION - CARMEN ZAHARIA (Journal of Engineering Studies and Research)
Nowadays, an interdisciplinary field of engineering that focuses on analytical and/or empirical models represented by mathematical, data-driven and biotic structures combined with physical, biological and ecological processes in water, air and eco-systems is developing, i.e. environmental system engineering (ESE). In this system, environmental modeling and process optimization acts together for solving problems with environmental systems, especially for minimizing pollution, or eco-toxicological effects. The present paper proposes the study of modeling and optimization of an environmental system (i.e. textile wastewater treatment system based on sorption onto indigene peat) for its discoloration (consequently, decreasing of color, organic and inorganic loads of effluent discharged in aquatic receptor, or inside reused). All performed laboratory tests consisted in 22 hours-sorption experiments onto peat applied for a real colored textile effluent, organized with respecting of an empirical planning by a central active composite rotatable 23 order design, considering as independent variables the peat dose (X1), pH (X2), and temperature (X3), and as optimization criterion, or decision function, the discoloration degree, or color removal (Y, [%]). The mathematical model was found adequate for the textile wastewater treatment, and the optimal operational conditions for highest discoloration efficiency were proposed.